2010
DOI: 10.1001/archneurol.2010.86
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in the Surgical Management of Intractable Temporal Lobe Epilepsy in the United States

Abstract: To determine whether, over a long time span, race and/or other predictive factors for patients with intractable temporal lobe epilepsy (TLE) who receive anterior temporal lobectomy (ATL) exist on a national level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
59
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 36 publications
6
59
2
Order By: Relevance
“…We found that racial minorities were significantly less likely to receive surgical treatment than white individuals, and patients with Medicare or Medicaid had surgery at notably lower rates than those with private insurance. Previous studies have also found similar inequalities in the epilepsy surgery, noting in particular underutilization among black patients, 14,37 as well as significant treatment disparities by socioeconomic status. 14,38,39 While the reasons for this disparity are not fully understood, we did observe that white patients were more likely to have private insurance than nonwhite individuals.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…We found that racial minorities were significantly less likely to receive surgical treatment than white individuals, and patients with Medicare or Medicaid had surgery at notably lower rates than those with private insurance. Previous studies have also found similar inequalities in the epilepsy surgery, noting in particular underutilization among black patients, 14,37 as well as significant treatment disparities by socioeconomic status. 14,38,39 While the reasons for this disparity are not fully understood, we did observe that white patients were more likely to have private insurance than nonwhite individuals.…”
supporting
confidence: 58%
“…Previous studies have also found similar inequalities in the epilepsy surgery, noting in particular underutilization among black patients, 14,37 as well as significant treatment disparities by socioeconomic status. 14,38,39 While the reasons for this disparity are not fully understood, we did observe that white patients were more likely to have private insurance than nonwhite individuals. Therefore, it is possible that lower rate of surgery among racial minorities is influenced by access to care or financial considerations of treating institutions.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Although studies have demonstrated sociodemographic disparities in the utilization of temporal lobectomy, none have examined whether such factors mediate delays in time to surgery in children. [14][15][16][17] To elucidate factors associated with timing of referral and surgery among children with epilepsy, we utilized a large cohort from the University of California, Los Angeles (UCLA) who had surgery over the past 25 years. Based on prior literature in children and adults, we hypothesized that increased epilepsy severity as documented by a history of IS and a greater seizure frequency, abnormal pre-referral brain MRI, private insurance, and non-Hispanic, white race/ethnicity would be associated with shorter time to surgery.…”
mentioning
confidence: 99%
“…4 There are racial, ethnic, and socioeconomic disparities in access to treatment, especially surgery. 5 A lack of specialty care may lead to delayed recognition of seizures and inadequate treatment. 6 Thus, there is a large disparity between care that should be delivered and the care that is actually delivered.…”
mentioning
confidence: 99%